Audiovisual content and distance teaching university: a methodological proposal - Rodríguez Bravo, Ana Eva; Tasende Mañá, Beatriz; González Olivares, Angel Luis; Muelas Plaza, Alvaro; de Juanas Oliva, Angel (Historia y Comunicación Social, 2014)
The current paradigm of new technologies makes educational activities aimed at developing new spaces for communication and open distribution of audiovisual media for teaching. In this paper, we present a methodology for the integration of audiovisual content to university distance. It takes place during the year 2013 under the subject “The adult learning in the knowledge society” that is taught in the Master of Educational Intervention on Social Contexts of the Faculty of Education (UNED).